LEGISLATIVE EVALUATION OF LABOR REFORMS PROMOTED THROUGH PROVISIONAL PRESIDENTIAL DECREES IN THE BOLSONARO’S GOVERNMENT - Gaspardo, Murilo [UNESP]; Santos, Letícia Rezende [UNESP]; Marchioni, Artur [UNESP] (FapUNIFESP (SciELO), 2023)
Since the impeachment of Dilma Rousseff, a series of structural changes have been implemented in Brazil. Within the scope of Labor Law, still under the Temer Government, Laws ns. 13.429/2017 and 13.467/2017 were approved. And, in the first year of the Bolsonaro Government, these reforms were intensified with the issuance of Provisional Presidential Decrees ns. 870/2019, 873/2019, 881/2019 and 905/2019. Considering the stated objective of these legislative changes, namely the increase of employment, the specific aim of this article is to answer the following question: what were the impacts of changes in labor legislation promoted by the PPD’s edited by Bolsonaro’s Government during the first year of its term? Therefore, legislative evaluation was used as a method of approach, and literature review, document analysis and the systematization of indicators on employment, working conditions and economy, as research techniques. From this analysis it was extracted that the changes introduced by the Provisional Presidential Decrees, in addition to not translating into better economic performance, result in the deterioration of working conditions, summarized in: I) disarticulation of structures for planning policies related to Labor Law; II) devaluation of unions; III) flexibilization of labor rights; and IV) weakening of inspection bodies and norms.
Avaliação legislativa das reformas trabalhistas promovidas por meio de medidas provisórias no Governo Bolsonaro
Keywords: Bolsonaro Government; labor reform; legislative evaluation; Provisional Presidential Decree; Workers’ rights